2020
DOI: 10.3390/su12104067
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and Bodily Pain in Older Women Participants in a Physical Education Program. A Multiple Moderated Mediation Analysis

Abstract: (1) Background: Bodily pain is normally associated with the consequences of ageing, whereas anxiety shows a high prevalence in elderly people, decreasing the health-related quality of life (HRQoL). Pain coping strategies are used to reduce the consequences of pain, specifically in older people. This study analyzed if the passive and active pain coping strategies were significant moderators in the link between anxiety and bodily pain with a physical component as a mediator. (2) Methods: This cross-sectional stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
0
0
Order By: Relevance
“…Vergne-Salle et al [27] found that 38.4% of patients continued to endure moderate to severe pain despite biological treatment, observing a strong correlation between pain and depression and anxiety, which subsequently impacts work, sleep, and mood. Depression and anxiety related to chronic pain are often tied to cognitive and behavioral processes like catastrophizing [1] and passive coping styles [28,29]. As a result, the processes that drive stress responses in RA patients can be subtle [5,30].…”
Section: Plos Onementioning
confidence: 99%
“…Vergne-Salle et al [27] found that 38.4% of patients continued to endure moderate to severe pain despite biological treatment, observing a strong correlation between pain and depression and anxiety, which subsequently impacts work, sleep, and mood. Depression and anxiety related to chronic pain are often tied to cognitive and behavioral processes like catastrophizing [1] and passive coping styles [28,29]. As a result, the processes that drive stress responses in RA patients can be subtle [5,30].…”
Section: Plos Onementioning
confidence: 99%